Salient compromises in the newsvendor game - Markus Dertwinkel-Kalt; Mats Köster (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
The newsvendor problem denotes the puzzle that a retailer facing an uncertain demand for some product underreacts to profit margins, and hence adjusts the order quantity toward the expected demand. Due to its range of applications in operations management, this problem has drawn much interest in recent years. Various articles have tried to reconcile the newsvendor problem with loss aversion under ad hoc assumptions on the underlying reference point. We, instead, argue that the newsvendor problem is an application of the well-studied compromise effect. As the compromise effect is based on violations of the IIA axiom, we argue that models of context-dependent behavior, such as salience theory, better explain newsvendor-like behavior than loss aversion-based models. We conduct a novel experiment which allows us to clearly distinguish between the role of loss aversion and salience, and find strong support for the latter. Thereby, we also add to the agenda of comparing loss aversion-based models and salience theory.
Keywords: D03; 330; Newsvendor Problem; Loss Aversion; Salience; Compromise Effects